2015
DOI: 10.1080/02701367.2014.999189
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Motivational Climate Interventions on Psychobiosocial States in High School Physical Education

Abstract: Purpose: The purpose of this study was to examine the effects of task-and ego-involving climate manipulations on students' climate perception and psychobiosocial (PBS) states in a physical education setting. Method: Two subsamples of female students (N = 108, 14-15 years of age) participated for 12 lessons on either a task-or an ego-involving climate intervention as grounded in the TARGET model. Results: At the end of the treatment, the participants of the ego-involved group reported lower scores in perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 28 publications
7
38
0
10
Order By: Relevance
“…The items of the scale are those proposed for an individualized profiling of high-level athletes [8]. Although non-standardized scales measuring athletes’ psychobiosocial states have actually been used for research and applied purposes in sport [28, 29] and physical education [24] settings, the validity and reliability of these scales was not previously established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The items of the scale are those proposed for an individualized profiling of high-level athletes [8]. Although non-standardized scales measuring athletes’ psychobiosocial states have actually been used for research and applied purposes in sport [28, 29] and physical education [24] settings, the validity and reliability of these scales was not previously established.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, functional states mediated the effect of technical and cognitive self-efficacy on performance of carom billiards players [29]. In the physical education context [24], results showed that achievement motivational climates induced by teachers tend to determine in their students states consistent with the motivational atmosphere, thus supporting the advantages of a task-involving climate to enhance pleasant emotional experiences. The research benefits deriving from assessing psychobiosocial states highlight the need of a reliable and valid measure.…”
Section: Introductionmentioning
confidence: 99%
“…Instructors may promote either of the two major motivational climates (Bortoli, Bertollo, Vitali, Filho, & Robazza, 2015). Mastery climate is encouraged by instructor's focus on cognitive ability, effort and self-improvement (Ames, 1992;Roberts, Treasure, & Conroy, 2007).…”
Section: Motivational Climatementioning
confidence: 99%
“…Studies have reported that attitudes and intercommunications are elements which are engaging in motivational climate, for instance interactive motivation between peers, based on the intention to foster competition, encouragement, collaboration and endearment (Beltman & Volet, 2007;Bengoechea & Strean, 2007;Keegan, Harwood, Spray, & Lavallee, 2009;Keegan et al, 2010;Vazou, Ntoumanis, & Duda, 2005;Weiss, Amorose, & Wilko, 2009). The positive outcomes of mastery climate are numerous, because its main emphasis is given to learning and cooperation (Bortoli, Bertollo, Vitali, Filho, & Robazza, 2015). The students are emboldened with advanced abilities, cooperative learning, personal enrichment and commending for each endeavor (Ames, 1992a;Roberts et al, 2007).…”
Section: Aggressive Communicationmentioning
confidence: 99%
“…Moreover, expanded research has indicated mastery's climate positive relation with accomplishments, satisfaction, importunity in every attempt, flexibility (Ntoumanis & Biddle, 1999;Roberts, 2012;Van De Pol, Kavussanu, & Ring, 2012), as well as decreased anxiety, commitment, engagement, enthusiasm, assurance, integrity (Atkins et al, 2015;Braithwaite, Spray, & Warburton, 2011;Cunningham & Xiang, 2008;Kavussanu & Roberts, 1998;Mouratidis, Vansteenkiste, Lens, & Vanden Auweele, 2009;. Performance motivational climate is based essentially on social comparison and competition, arousing negative emotions on students such as nervousness and distraction (Bortoli et al, 2015;Liukkonen, Barkoukis, Watt, & Jaakkola, 2010). Throughout the course that focuses on performance motivational climate, teachers emphasize on regulative assessment, display of students' abilities and praising their best efficiency (Ames, 1992b;Ames & Archer, 1988;Keegan et al, 2010;Murcia, Camacho, & Rodríguez, 2008).…”
Section: Aggressive Communicationmentioning
confidence: 99%